Motivasi Kerja Badan Musyawarah Kampung dalam Pelaksanaan Pembangunan - hesty tambajong; Dewi Putri Anjar Wulan (SOCIETAS, 2020)
This article aims to determine the work motivation of the role of the Village Deliberative Council(Bamuskam) in Yanggandur and Kuper villages and to identify factors that have an impact on the role ofthe Village Deliberative Council (Bamuskam) in implementing development. By using a qualitativedescriptive type, namely the type of research that explores and clarifies an event or phenomenon in socialfacts. The results obtained indicate that the work motivation of the Village Deliberative Council(Bamuskam) in Yanggandur and Kuper villages is optimal in carrying out development in their respectivevillages. Members of the Yanggandur and Kuper Bamuskam who are motivated or compelled to do a jobwill have the enthusiasm to do their job in building the village. In carrying out development, Bamuskambecomes a forum for accommodating and channeling community aspirations, and also as a supervisor ofthe performance of the Village Head in relation to the Bamuskam function regarding supervision. Inaddition, there are several factors that affect the function and role of the Village Deliberative Council(Bamuskam) in carrying out development which consists of supporting factors, namely the education levelof Bamuskam members during the selection process for Bamuskam members, community factors, factorsof cooperation with village officials, and social factors culture. As for the inhibiting factor, namely theabsence of a Bamuskam secretariat office both in Yanggandur Village and Kuper Village.